Analysis of the delay of A380 project from project management perspective. - Nguyen, Quoc Linh. (2010)
Project Delay is not a rare phenomenon and causes huge loss especially to complex and mega projects. Recently, A380, the biggest aviation project, which aims at producing the largest airplane in the world, has also experienced delay that cost several billions dollars in loss. Project delay problem has been researched for years and achieved many important results, but investigation of mega project delay was not at that level. In order to analyze project delay effectively, a framework needs to be used to enlighten complex issues, mutual relationships, interactions of a mega project to find out ultimate reasons of delay. However, there is a gap in finding such framework for analyzing delay root causes of mega projects and serving project managers as a prediction tool for considering the factors that can affect project's completion date. This dissertation aims at creating the framework for the above purpose to analyze the delay of A380 projects and serve as tools for future use of project managers.